2019
DOI: 10.1002/ejoc.201901000
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 8‐Hydroxyphenanthridines by Microwave‐Mediated IMDAF Reactions; Synthesis Directed towards Lycorine Alkaloids

Abstract: 8‐Hydroxyphenathridines have been synthesized efficiently from N‐propargyl‐ortho‐furylanilines employing microwave‐mediated one‐pot intramolecular Diels–Alder reaction on furans (IMDAF) reaction and subsequent aromatization. The 8‐hydroxyphenathridines were also subjected to further functionalization; O‐alkylation and conversion to the corresponding triflate followed by Suzuki coupling. N‐Propargyl‐7‐furylindole and the corresponding indoline also underwent smooth IMDAF cyclization to give, after rearomatizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Additional references are cited within the Supporting Information. [21][22][23][24][25][26][27] The Supporting Information contains description of DFT calculations and procedures and spectral data for all novel compounds as well as copies of 1 H and 13 C NMR spectra of all novel compounds. ChemistryOpen…”
Section: Supporting Information Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Additional references are cited within the Supporting Information. [21][22][23][24][25][26][27] The Supporting Information contains description of DFT calculations and procedures and spectral data for all novel compounds as well as copies of 1 H and 13 C NMR spectra of all novel compounds. ChemistryOpen…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…We have developed a synthetic route to phenanthridines with a microwave‐mediated IMDAF reaction of allylamino‐ ortho ‐furylarenes as a key‐step [12] . Later, we showed that propargylamino‐ ortho ‐furylarenes cyclized to 8‐hydroxyphenanthridines [13] . The hydroxyl group in the 8‐position offers possibilities for further functionalization in the C‐ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By conveniently reacting N-alkyl-ortho-furylanilines 238, 239 and 240 in the presence of catalytic amounts of hydrochloric acid (Scheme 57), the formation of the annulated 5/6/6/6-ring system is achieved in one step via an endo-selective [4+2]-cycloaddition followed by a cycloreversion. 80 Scheme 57 A microwave-assisted intramolecular Diels-Alder reaction on furans (IMDAF) conveniently yields 8-hydroxyphenanthridines 235, 236 and 237 5 Syntheses from 2020…”
Section: Special Topic Synthesis 413 Synthesis Of Tetrahydropyrazolo[4′3′:56] Pyrano[34-c]quinolonesmentioning
confidence: 99%
“…By conveniently reacting N -alkyl- ortho -furylanilines 238 , 239 and 240 in the presence of catalytic amounts of hydrochloric acid (Scheme 57 ), the formation of the annulated 5/6/6/6-ring system is achieved in one step via an endo -selective [4+2]-cycloaddition followed by a cycloreversion. 80…”
Section: Syntheses From 2019mentioning
confidence: 99%